2021
DOI: 10.3389/fcell.2021.639111
|View full text |Cite
|
Sign up to set email alerts
|

Serine Metabolism Regulates YAP Activity Through USP7 in Colon Cancer

Abstract: Metabolic reprogramming is a vital factor in the development of many types of cancer, including colon cancer. Serine metabolic reprogramming is a major feature of tumor metabolism. Yes-associated protein (YAP) participates in organ size control and tumorigenesis. However, the relationship between YAP and serine metabolism in colon cancer is unclear. In this study, RNA sequencing and metabolomics analyses indicated significant enrichment of the glycine, serine, and threonine metabolism pathways in serine starva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“… 1 , 13 , 14 Altered cellular energy metabolism reprogramming is emerging as a key hallmark of tumor cells and malignant transformation and one of the key initiating events in carcinogenesis. 15 , 16 , 17 Glucose is a major source of energy in mammalian cells because it generates ATP through intermediate glycolytic metabolites. 16 , 18 In tumor cells, glucose uptake is dramatically increased by the upregulation of glycolytic enzymes such as hexokinase 2 (HK2), 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3/4 (Pfkfb3/4), lactate dehydrogenase A (LDHA) and the expression of glucose transporters (Gluts, particularly Glut1) to fuel aerobic glycolysis and provide cellular metabolites for the generation of new biomass, which ultimately stimulates tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 13 , 14 Altered cellular energy metabolism reprogramming is emerging as a key hallmark of tumor cells and malignant transformation and one of the key initiating events in carcinogenesis. 15 , 16 , 17 Glucose is a major source of energy in mammalian cells because it generates ATP through intermediate glycolytic metabolites. 16 , 18 In tumor cells, glucose uptake is dramatically increased by the upregulation of glycolytic enzymes such as hexokinase 2 (HK2), 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3/4 (Pfkfb3/4), lactate dehydrogenase A (LDHA) and the expression of glucose transporters (Gluts, particularly Glut1) to fuel aerobic glycolysis and provide cellular metabolites for the generation of new biomass, which ultimately stimulates tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced expression and nuclear localization, and decreased phosphorylation of YAP are frequently observed in many types of tumors and is also considered a novel prognostic marker and therapeutic target in osteosarcoma 1,13,14 . Altered cellular energy metabolism reprogramming is emerging as a key hallmark of tumor cells and malignant transformation and one of the key initiating events in carcinogenesis 15–17 . Glucose is a major source of energy in mammalian cells because it generates ATP through intermediate glycolytic metabolites 16,18 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Previous studies have reported possible relevance of UHRF1 to the regulation of YAP1. Ubiquitin-specific protease 7 (USP7), which binds to UHRF1 in a complex to stabilize and promote UHRF1 function, 29 has been demonstrated to increase YAP stability by regulating its deubiquitination and degradation in CRC 30 and HCC. 31 In cervical cancer, the knockdown of Forkhead Box M1 (FOXM1), a transcription factor of UHRF1, 32 could activate the Hippo-YAP1 pathway by inhibiting the nuclear translocation of YAP1.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), USP7 was reported to promote serine deprivation resistance. Low concentration of cellular serine was found to suppress the expression of USP7 through an unknown mechanism [ 66 ]. USP7 deubiquitinates and stabilizes Yes-associated protein (YAP), which activates downstream signaling pathways and promotes cell proliferation [ 66 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%